2021
DOI: 10.38150/sajeb.11(2).p176-182
|View full text |Cite
|
Sign up to set email alerts
|

Study of the biological and epidemiological profile of breast cancer in Western Algeria

Abstract: Despite recent progress and therapeutic advances made in the field of breast cancer. This pathology remains the main cause of female cancer and repre-sents a real major public health problem in Algeria as well as globally. The objective of this study, carried out in the Algerian West, was to assess the epidemiological profile of breast cancer in the Oran region through the pa-tients recruited in the Regional Military Hospital of Oran University (HMRUO), then to determine the clinical, biological and pathologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…Tumor size in Tunisia declined from 4.9 cm in 1991 30 to 3 cm in 2017 31 and 2.5 cm in our series but is still greater than BC's size in Western countries which is reduced to 1.5 cm under the effect of mass screening and early detection campaigns 32 . In Algeria, a recent study reported a mean tumor size of 3.6 cm 33 . In Algeria and Tunisia, BC mainly concerns a young population, thus mammographic screening should start at the age of 40.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Tumor size in Tunisia declined from 4.9 cm in 1991 30 to 3 cm in 2017 31 and 2.5 cm in our series but is still greater than BC's size in Western countries which is reduced to 1.5 cm under the effect of mass screening and early detection campaigns 32 . In Algeria, a recent study reported a mean tumor size of 3.6 cm 33 . In Algeria and Tunisia, BC mainly concerns a young population, thus mammographic screening should start at the age of 40.…”
Section: Discussioncontrasting
confidence: 60%
“… 32 In Algeria, a recent study reported a mean tumor size of 3.6 cm. 33 In Algeria and Tunisia, BC mainly concerns a young population, thus mammographic screening should start at the age of 40.…”
Section: Discussionmentioning
confidence: 99%